2018
DOI: 10.15581/004.35.557-577
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Value of Service Learning: Students’ assessments of Personal, Procedural and Content Learning

Abstract: Este artículo se enmarca en el proyecto I+D+i EDU2014-55354-R, titulado Formación universitaria: análisis del proceso de aprendizaje y cambio identitario a través del aprendizaje-servicio en comunidades de prácticas en contextos de exclusión, fi nanciado por la Secretaría de Estado de investigación, Desarrollo e Innovación, durante los años 2015-2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Studies evidence that SL experiences make a positive impact on students [2], in particular on the perception of their role as agents of social change [3,4] as well as on faculty [5]. It is a first step towards responsible and global citizenship, particularly when SL projects are targeted to communities with disabilities or specific needs of educational support [6,7].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies evidence that SL experiences make a positive impact on students [2], in particular on the perception of their role as agents of social change [3,4] as well as on faculty [5]. It is a first step towards responsible and global citizenship, particularly when SL projects are targeted to communities with disabilities or specific needs of educational support [6,7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…3. identify motivational factors in university students to achieve Sustainable Development Goal 4 (Quality Education) with the service-learning project. 4.…”
mentioning
confidence: 99%
“…Elyer and Giles (1999) reported that students who participated in SL projects enjoyed their courses, reported substantial learning, and made efforts to seek out further similar engaging experiences. Garcia- Romero et al (2018), by using the Course Value Inventory scale, showed relevant differences between service-learning and other models of practice from the perspective of students. Students reported higher satisfaction, better perception of personal change and skills acquisition.…”
Section: Service-learning and Studentsmentioning
confidence: 99%
“…As also stated by Eyler and Gilles (1994), even limited experience may help reshape the way students think about obligations and opportunities for service. Garcia- Romero et al (2018) have shown that the SL experience has been perceived by the students as relevant for personal change and the learning of professional skills.…”
Section: Students' Narratives On the Satisfaction With Service-learni...mentioning
confidence: 99%
“…Siguiendo el análisis realizado por Eyler et al (2001) se pueden distinguir claramente diferentes temáticas en la investigación sobre el ApS y su implementación. Desde aquellas que analizan los criterios de calidad que deben poseer los proyectos de ApS, la institucionalización de dicha metodología, sus dimensiones y modelos (Heras-Colàs et al, 2017), hasta las centradas en las percepciones de los diferentes actores implicados (docentes, directivos, estudiantes…), así como el impacto que el ApS ha generado, fundamentalmente, en el alumnado (García-Romero et al, 2018). Es, justamente, esta última temática la que centra nuestro interés, dado que, si pretendemos crear una sociedad innovadora, inclusiva y responsable, la universidad deberá capacitar a los futuros profesionales para que sean más justos, estén más comprometidos con su profesión, más implicados con la sociedad que les rodea y dispuestos a facilitar las transformaciones sociales desde su entorno más próximo (Hernández & Miguel, 2017).…”
Section: Introductionunclassified